(untitled) (Research, Society and Development, 2020)
The Brazilian schools have been facing big difficulties in promoting social access to deaf people because they do not have the necessary structured and qualified professionals to work with different needs. As an example, it is possible to mention some problems faced by deaf students on the school environment such as the difficulty of using Libras (Brazilian Sign Language) in schools and the lack of teaching methodologies appropriate to their reality. This challenge becomes even bigger because for a long time Libras did not have the necessary attention and the communication with deaf people was not carried out in a good way. The aim of this article is to show the difficulties concerning the inclusion of deaf students in the school environment and to present some methods to try to solve the problems that were found. For deaf people it is extremely important to have access to adapted materials in order to follow the subjects taught in the classroom and to be helped in their learning process. The qualitative methodology was used on this paper to analyze the data that were already collected and, as a result, some studies are being carried out in order to try to solve the difficulties found and to normally allow the access of deaf people in regular schools, in chemistry classes.